ESP 8266-Based Car Battery Current and Voltage Monitoring Design - Reynaldo; Winoko, Yuniarto Agus (Evrimata: Journal of Mechanical Engineering, 2024)
Fluctuations in engine speed can make motorists unaware of the actual battery voltage and current, even though the battery voltage should be above 85% of the maximum voltage. Typically, the battery voltage for petrol engines is around 12.5 Volts in order to function properly. This study aims to calculate the changes in current and voltage at various loads when the engine rotation is at 1000, 1500, 2500, 3000, 3500, and 4000 rpm. Measurements were made using the ESP8266 microcontroller and compared with measurements using a multimeter. Data was taken by measuring the current and voltage of the battery when the engine was loaded by AC, audio, and lights. The test results show that the voltage measured with a multimeter tends to be higher than that measured with a smartphone. The voltage measured by the multimeter increased from 1000 to 2000 Rpm, decreased at 2500 Rpm, and increased again up to 4000 Rpm. When measured with a smartphone, the voltage tends to be stable from 1500 to 3000 Rpm, and then increases at 3500 and 4000 Rpm. The charging system shows an increase in fulfilled electricity demand at each revolution.